Sistem Informasi Berbasis Web Untuk Pemetaan Geografis Lahan Pertanian (Studi Kasus : Desa Darmasari Kecamatan Sikur Lombok Timur) - Suhartini Suhartini; Hadian Mandala Putra; Muhammad Saipul; Lalu Kerta Wijaya (Infotek: Jurnal Informatika dan Teknologi, 2023)
The potential of agricultural land in Indonesia is still extensive, so the agricultural sector is still one of the incomes for most Indonesians. The agricultural land sector is widespread in various regions in Indonesia, one of which is in Darmasari Village, Sikur District. As an agricultural area, most of the population in Darmasari Village chooses livelihood as farmers. However, the distribution of agricultural land has not been mapped, which can provide information about the location of agricultural land, especially those in Darmasari Village. In this study, a web-based Agricultural Land Geographic Information System was constructed in Darmasari village. The geographic information system that is built can display information in the form of spatial and non-spatial data that describes an object based on the state of the earth. The method used in creating this system is to use the object-oriented method. With the construction of this Geographic Information System, it is hoped that it will be able to provide information for the community about the distribution of the location and area of agricultural land, especially in the Darmasari Village area